Detection of ESBL-Encoding Genes in Antibiotic-Resistant Escherichia coli Isolated from Houseflies (Musca domestica) in Campus Food Court - Lukman, Denny Widaya; Pisestyani, Herwin; Aminudin, Muhammad Rizki; Supriyono, Supriyono; Sukmawinata, Eddy (Jurnal Sain Veteriner, 2025)
Escherichia coli is a dangerous pathogen that is reported to bring about disease in humans as well as animals. E. coli is commonly associated with diseases due to food contamination. Some strains of the pathogen have shown resistance to various antibiotics, one of them is ESBL-E. coli, leading to complex problems in health. The transmission of pathogenic bacteria in the environment can be mediated by houseflies (Musca domestica). This study aimed to analyze the presence of antibiotic-resistant E. coli bacteria and detect resistance genes carried by houseflies (M. domestica) collected from food courts in IPB University, Dramaga Bogor, Indonesia. The study included isolation and identification of E. coli bacteria based on ISO 16649-2: 2001 standards. E. coliisolates are then tested for antibiotic sensitivity using the Kirby Bauer disc diffusion method based on CLSI in 2023. Antibiotics tested included ciprofloxacin, ampicillin, tetracycline, trimethoprim-sulfamethoxazole, chloramphenicol, ceftazidime, and cefotaxime. Then, the identification of genes encoding ESBL resistance (blaCTX, blaTEM, and blaSHV) was conducted. The study found 5 isolates (5/40; 12.5%). Total 4 isolates of 5 isolates indicated resistance against two or several antibiotics tested. Detection of genes encoding ESBL resistance in 5 E. coli isolates showed that 2 isolates (40%) were positive for the blaTEM gene but did not show positive results for blaCTX and blaSHV genes. The appearance of antibiotic-resistant E. coli in houseflies in food court in campus should be taken into account.